2016
DOI: 10.3389/fnana.2016.00041
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Changes in Functional Connectivity in Posteromedial Cortex Subregions during the Progress of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder which causes dementia, especially in the elderly. The posteromedial cortex (PMC), which consists of several subregions involved in distinct functions, is one of the critical regions associated with the progression and severity of AD. However, previous studies always ignored the heterogeneity of the PMC and focused on one stage of AD. Using resting-state functional magnetic resonance imaging, we studied the respective alterations of each subre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
6
18
1
Order By: Relevance
“…Moreover, these functional disruptions have been described in relation to an early and restricted involvement of the ventral PCC network, followed by subsequent cascades to the dorsal PCC at the AD dementia stage (Mutlu et al, ). However, we found the functional connectivity of the dorsal PCC was more prominently affected in AD, which is in accordance with a recent study showing that functional connectivity alterations originated in the dorsal PCC and later expanded to the ventral PCC region in severe AD cases (Wu et al, ). Recent work has also shown the dorsal PCC to be an integrative nexus of cortical connectivity responsible for modulating cognitive control processes (Leech et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, these functional disruptions have been described in relation to an early and restricted involvement of the ventral PCC network, followed by subsequent cascades to the dorsal PCC at the AD dementia stage (Mutlu et al, ). However, we found the functional connectivity of the dorsal PCC was more prominently affected in AD, which is in accordance with a recent study showing that functional connectivity alterations originated in the dorsal PCC and later expanded to the ventral PCC region in severe AD cases (Wu et al, ). Recent work has also shown the dorsal PCC to be an integrative nexus of cortical connectivity responsible for modulating cognitive control processes (Leech et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that these abnormalities may underpin a precuneus‐hippocampal disconnection, and functional reductions in connected regions to the anterior cingulate (Sheline et al, ). Taken together, our findings concur with previous studies showing that different subregions of the PMC exhibit a differential vulnerability to AD (Petrella, Prince, Wang, Hellegers, & Doraiswamy, ; Wu et al, ; Xia et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Comparing to healthy controls, AD patients show reduced activations in area V5 and parietal-occipital cortex in a previous functional magnetic resonance imaging study16. Recently, there is an emerging view that many neurological disorders including AD might be critically associated with altered cortical connectivity171819 and disrupted neural inhibition22021. However, the functional relevance of these impaired inhibitory processing on the perceptual dysfunctions in AD remains largely elusive.…”
mentioning
confidence: 95%